2021
DOI: 10.1016/j.nicl.2021.102617
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state brain oscillations predict cognitive function in psychiatric disorders: A transdiagnostic machine learning approach

Abstract: Highlights Resting EEG activity associated with cognitive function in psychiatric disorders. Using EEG, random forest modeling predicts cognitive performance but not diagnosis. High alpha oscillations associated with better episodic memory and processing speed. Beta oscillations associated with worse performance in several cognitive domains. EEG power changes in psychiatric disorders may be related to cognitive dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Theta rhythm was found in multiple cerebral regions and was related to multiple cognitive functions, e.g., working memory, episodic memory, and executive function ( 54 , 55 ). Normal theta rhythm oscillation is considered a predictor of good performance in executive function ( 56 ). Human brain imaging studies have shown enhanced coupling of theta oscillations between the hippocampus and DLPFC during cognitive activity ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Theta rhythm was found in multiple cerebral regions and was related to multiple cognitive functions, e.g., working memory, episodic memory, and executive function ( 54 , 55 ). Normal theta rhythm oscillation is considered a predictor of good performance in executive function ( 56 ). Human brain imaging studies have shown enhanced coupling of theta oscillations between the hippocampus and DLPFC during cognitive activity ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, if observed during task within specific task relevant brain areas, it would index processes related to the particular task or experimental situation. Alpha power at rest has been found to be positively correlated with task performance in cognitive control (Mahjoory et al, 2019) and episodic memory (Sargent et al, 2021) tasks, but negatively correlated with language skills (Kwok et al, 2019). This somewhat non-univocal picture suggests that for different experimental situations, different levels of pre-inhibition and disinhibition of cortical areas are beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Third, another promising area focuses on transdiagnostic approaches to uncover neural correlates of specific domains (such as cognition, arousal, and emotion regulation), which have been implicated in psychopathology across the diagnostic spectrum. 49 Recent ML efforts have been dedicated to identifying transdiagnostic brain dysfunctions and dimensions of psychopathology to improve understanding of comorbidity among psychiatric disorders. 50 , 51 , 52 , 53 Importantly, leveraging “big data” from a longitudinal perspective offers a promising way to track the neurobiological and phenotypic trajectories that have been rarely examined in previous cross-sectional psychiatric studies.…”
Section: How Can ML Help Psychiatry?mentioning
confidence: 99%